Correction: Bakr et al. Efficacy of Quercetin and Quercetin Loaded Chitosan Nanoparticles Against Cisplatin-Induced Renal and Testicular Toxicity via Attenuation of Oxidative Stress, Inflammation, and Apoptosis. Pharmaceuticals 2024, 17, 1384 - Alaa F. Bakr; Riham A. El-Shiekh; Mohamed Y. Mahmoud; Heba M. A. Khalil; Mohammad H. Alyami; Hamad S. Alyami; Omneya Galal; Dina F. Mansour (Pharmaceuticals)
Error in Figure [...]